Studi perilaku slit link pada sistem eccentrically braced frame (EBF) untuk kategori link pendek - Gokma Ferdinanta Sihombing; Jusuf Wilson Meynerd Rafael; Budi Suswanto (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Link beams in Eccentrically Braced Frame (EBF) systems are designed to act as energy dissipation components by undergoing controlled plastic deformation during seismic events. However, conventional links often experience high stress concentrations that may reduce their seismic performance. This study evaluates the influence of slit geometry on stress distribution, hysteretic response, deformation capacity, and ductility of short-link beams in EBF systems. Six slit-link models based on a WF 588×300×12×20 section were numerically investigated using the finite element method in Abaqus, consisting of three block-slit models (SL-B1, SL-B2, and SL-B3) and three parabolic-slit models (SL-P1, SL-P2, and SL-P3). Cyclic loading was applied following the AISC 341-22 loading protocol, while monotonic loading was used to generate backbone curves and ductility parameters. The results indicate that increasing slit spacing improves both ultimate strength and initial stiffness for all models. The ultimate capacity increased from 188.49 kN in model SL-B1 to 391.03 kN in model SL-B3 and from 201.39 kN in model SL-P1 to 456.45 kN in model SL-P3. Stress distribution analysis revealed that parabolic slits provide a more uniform stress distribution and lower stress concentration than block slits. Model SL-P3 exhibited the best overall performance with an ultimate capacity of 456.45 kN, a ductility factor of 2.94, and a Relative Energy Dissipation Factor (REDF) of 3.20. Failure mechanisms were concentrated within the slit region without significant yielding in the flange or end-plate components. The findings demonstrate that parabolic slit configurations can significantly enhance the strength, ductility, and energy dissipation capacity of short-link elements in EBF systems compared with conventional block-slit configurations.